Characterisation of Commercial Li‐Ion Batteries Using Electrochemical Impedance Spectroscopy. Issue 10 (14th March 2022) - Ezpeleta, Ignacio; Freire, Lorena; Mateo‐Mateo, C.; Nóvoa, X. Ramón; Pintos, Aránzazu; Valverde‐Pérez, Sara
Abstract: Electrochemical impedance spectroscopy (EIS) was used to characterize commercial cylindrical Li‐ion cells under different state‐of‐charge (SOC) conditions and up to 300 charge/discharge cycles to monitor state‐of‐health (SOH) status. The study included the effect of temperature to access better resolution of the time constants related to the redox reactions at the electrodes. The EIS in the 10 kHz–1 mHz frequency range allowed the elaboration of a comprehensive electrical equivalent that incorporated the geometry of the cell and the electrochemical processes occurring at the anode and cathode active material. The fitting procedure of the experimental EIS data to the equivalent circuit produced parameter values that can be used to assess the SOC and SOH of the cell. In the study example, early detection of cell degradation can be obtained using the evolution of Li + diffusion resistance through the solid electrolyte interface (SEI) layer. Abstract : Electrochemical impedance spectroscopy (EIS) performed over seven frequency decades allows kinetic parameter identification for the anode and cathode processes in Li‐ion batteries (LiBs). The charge transfer resistance and the diffusion resistance can be used for state of charge (SOC) and state of health (SOH) determination. A new electrical equivalent circuit is presented that allows proper identification of the various processes defining the impedance spectrum, including diffusion through the solid electrolyte interface (SEI).